2020
DOI: 10.1177/1129729820951047
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of posterior approach insertion of tunneled cuffed catheter: A single clinic retrospective analysis

Abstract: Background and objectives: For patients who rely on a tunneled cuffed catheter, the internal jugular vein is the preferred site of insertion. A few studies have suggested that the posterior approach for central lines is equivalent or better in comparison to the conventional central approach. However, there have been fewer studies examining tunneled cuffed catheter insertion using the posterior approach. We have performed many posterior insertions of tunneled cuffed catheters in our practice, and because the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This hypothesis is supported by the only comparative data on the subject; a recent single-centre uncontrolled study of 200 patients showed dysfunction-related TDC failure rates of 17% vs 31% for posterior and classic central IJ access respectively. 19 The incidence of catheter-related bacteraemia in our cohort was .39 episodes per 1000 catheter-days. Historically, catheter-related bacteraemia rates of 1.1-5.5 episodes per 1000 catheter-days were reported.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This hypothesis is supported by the only comparative data on the subject; a recent single-centre uncontrolled study of 200 patients showed dysfunction-related TDC failure rates of 17% vs 31% for posterior and classic central IJ access respectively. 19 The incidence of catheter-related bacteraemia in our cohort was .39 episodes per 1000 catheter-days. Historically, catheter-related bacteraemia rates of 1.1-5.5 episodes per 1000 catheter-days were reported.…”
Section: Discussionmentioning
confidence: 62%
“…This hypothesis is supported by the only comparative data on the subject; a recent single-centre uncontrolled study of 200 patients showed dysfunction-related TDC failure rates of 17% vs 31% for posterior and classic central IJ access respectively. 19…”
Section: Discussionmentioning
confidence: 99%
“…Only a relatively few studies using ultrasound-guided central vena catheterization (CVC) for hemodialysis via the posterior approach of the IJV have been reported previously. 10,11 The results suggest that the posterior approach for central lines is equivalent to, or better than, the conventional middle approach. There are some advantages to the posterior approach: first, the IJV usually lies central to the common carotid artery (CA), and thus, the artery lies medially to the IJV when the vein is punctured, which decreases the chance of puncturing the artery when compared to the middle approach; second, the catheter can gradually be inserted into the vein from a lateral direction, which results in a straighter course for tunneling; thirdly, the posterior approach does not cross the SCM muscle and consequently there is less pain and discomfort during and after the procedure.…”
Section: Introductionmentioning
confidence: 92%
“…There are some advantages to the posterior approach: first, the IJV usually lies central to the common carotid artery (CA), and thus, the artery lies medially to the IJV when the vein is punctured, which decreases the chance of puncturing the artery when compared to the middle approach; second, the catheter can gradually be inserted into the vein from a lateral direction, which results in a straighter course for tunneling; thirdly, the posterior approach does not cross the SCM muscle and consequently there is less pain and discomfort during and after the procedure. 11 However, the posterior approach of the IJV has been rarely reported for TIVAPs, and it is still overlooked.…”
Section: Introductionmentioning
confidence: 99%